Human-centered design of e-health technologies concepts, methods and applications - Ziefle, Martina Cornelia 1962-; Röcker, Carsten 1975- (Premier reference source, 2011)
Unites researchers and industry practitioners from different disciplines to share their domain-specific knowledge and contribute to a holistic introduction into the area of human-centered design for e-health applications